1994
DOI: 10.1016/0954-6111(94)90042-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduced protection against exercise induced bronchoconstriction after chronic dosing with salmeterol

Abstract: The purpose of the present study was to assess the degree of protection of inhaled salmeterol against exercise-induced bronchoconstriction (EIB) after chronic compared with single dosing in patients with asthma. Twelve patients with exercise-induced asthma took part in a randomized double-blind crossover study to compare the duration of action of inhaled salmeterol 50 micrograms twice daily for 4 weeks with that of placebo. A standardized exercise test was performed at 6 h and 12 h after dosing on the first an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(98 citation statements)
references
References 19 publications
4
93
0
1
Order By: Relevance
“…Recent studies have shown that 2-4 weeks regular treatment with 50 µg twice daily reduced the protective effect of the drug against EIA [33] and cold air challenge [34]. The design of the present study excluded the possibility of this phenomenon, in fact no patient had used salmeterol regularly.…”
Section: Discussionmentioning
confidence: 76%
“…Recent studies have shown that 2-4 weeks regular treatment with 50 µg twice daily reduced the protective effect of the drug against EIA [33] and cold air challenge [34]. The design of the present study excluded the possibility of this phenomenon, in fact no patient had used salmeterol regularly.…”
Section: Discussionmentioning
confidence: 76%
“…As inhaled long-acting β 2 agonists rapidly loose their protective effect on exercise-provoked asthma when used on a regular basis (62)(63)(64), their use may not be advocated in subjects who exercise regularly in cold weather. For those subjects, leukotriene receptor antagonists may be more suitable since they are as effective as long-acting β 2 agonists in this setting (49,65) and do not loose their protective effect when used on a regular basis (63)(64)(65).…”
Section: Cold Air-provoked Short-term Responsesmentioning
confidence: 99%
“…However, prolonged use of salbutamol or terbutaline reduces the protection afforded against bronchoconstriction induced by methacholine [21][22][23], exercise [24] or antigen challenge [21,23] and has been shown to increase the magnitude of the late asthmatic response induced by allergen [25]. Similarly, regular treatment with salmeterol also leads to a loss in protection against bronchospasm induced by methacholine [26,27] and exercise [28]. Furthermore, β 2 -adrenoceptor agonists have been demonstrated to steepen the dose-response curve to methacholine [15,16].…”
Section: Discussionmentioning
confidence: 99%